Magic carpet race! - Finnegan, Delphine; Fruchter, Jason; Nickelodeon (Firm); Penguin Random House; Viacom International (New York Random House, 2017)
Twin sisters Shimmer and Shine learn lessons about teamwork with their best human friend, Leah, when they participate in a race
"Based on the teleplay "Zoom Zahramay" by Dustin Ferrer."
At head of title: Nickelodeon Shimmer and Shine
2
Keywords: JUVENILE FICTION / Girls & Women; JUVENILE FICTION / Media Tie-In; JUVENILE FICTION / Social Themes / Friendship; Jinn -- Juvenile fiction; Jinn; Picture books; Picture books; Racing -- Juvenile fiction; Racing; Teamwork (Sports); Teamwork (Sports) -- Juvenile fiction; Genies -- Fiction; Racing -- Fiction; Sisters -- Fiction; Teamwork (Sports) -- Fiction; Twins -- Fiction; Wishes -- Fiction; Genies -- Fiction; Wishes -- Fiction; Wishes -- Juvenile fiction; Fiction; Juvenile works; Readers (Publications.)